The Machiavellian reality of Leo Strauss - Vavouras, Elias (Dia-noesis: A Journal of Philosophy, 2024)
What is it makes Machiavelli such a decisive thinker, worthy of the Straussian interpretation? For Strauss, Machiavellian theoretical achievement is that he succeeds in misleading us, in leading us through his intelligent propaganda away from philosophy or political science in the literal sense of the word. He uses his interpretation of Machiavellian thought as a means of esoteric expression of his own positions. While he states that thoughts are expressed on Machiavelli, in fact Strauss' thoughts are expressed with Machiavelli as his "speaker-mouthpiece", with the aim of returning to the point where the Machiavellian rupture began, in classical natural right. As much as we agree or disagree with the Straussian interpretation, we cannot ignore the driving force it activates in the debate over the shaping of Machiavellian reality. After all, the Strauss’s analysis itself in the Machiavellian text aims at overcoming structural problems of the political thought and of the human condition in general.